The performing arts in a new era - McCarthy, Kevin F., 1945-; Brooks, Arthur C., 1964-; Lowell, Julia, 1961-; Zakaras, Laura; Rand Corporation; Pew Charitable Trusts (Santa Monica, CA : RAND, 2001)
What is the state of the performing arts in America at the turn of the 21st century? After decades of expansion, how are performing arts organizations faring? Has demand for live performances been increasing or decreasing? Are more Americans choosing the performing arts as a profession? And what is the likely effect of the Internet on the arts? The authors identify key trends affecting audiences, artists, arts organizations, and financing for all the performing arts. The most dramatic growth in demand for the performing arts has taken place in the market for recorded and broadcast performances. Live performances are increasingly provided by small performing groups at the community level--low-budget dance troupes, music groups, and theater ensembles that perform for little or no pay. In a few major cities, the largest and best-known organizations are growing even larger by focusing on star-studded productions that pull in the crowds. But conventional midsized arts organizations--once seen as the foremost purveyors of culture to middle America--are under significant financial stress. These and other trends suggest that policies that support artists and arts organizations may be less effective than strategies encouraging greater participation in the arts by a wider range of Americans in a wider range of art forms.
Introduction -- Conceptual Framework -- Historical Background -- Audiences for the Performing Arts -- Artists: Creators and Performers -- Characteristics of Performing Arts Organizations -- Financial Situation of Performing Arts Organizations -- Where Are the Performing Arts Headed?
Includes bibliographical references (p. 125-137).
Also available on the internet via WWW in PDF format.
Keywords: Arts and society -- United States; Performing arts -- Audiences -- United States; Performing arts -- United States -- Marketing; Performing arts -- United States